The multiple values of nature show the lack of a coherent theory of value—In any context - Kai M. A. Chan; Rachelle K. Gould; Cecily Maller; Robert Fish; Rosemary S. Hails; Kevin J. Gaston (People and Nature)
Abstract Pathways to sustainability require a broader and fuller representation of the multiple values of nature in policy and practice. In this People and Nature special feature entitled ‘The Multiple Values of Nature’, researchers interpreted all three key words differently: multiple, values and nature. The articles also engaged variously with concepts, theory, practice and data. In the face of this diversity, some see a burgeoning field and others see a mess. In this editorial, we characterize the diversity of these contributions and consider whether the field is poised to become mainstream. Specifically, we ask what might be limiting its efforts to unsettle the dominance of economic valuation. Like the broader field, the articles engage little with theory, and only one paper engaged with a theory of value (the dominant ‘utility theory’, rejecting a component of it). All articles thus seemed dissatisfied or disengaged with existing theories of value; this suggests that popular theories of value cannot properly account for the diversity of ways that people value and relate to nature. Perhaps there is a fundamental lack in how we understand value in any context (not just nature). As this fledgling field matures, we argue that building theory is key. Specifically, there is a need to articulate a theory of value to accommodate the multiple values of nature, which relates the various concepts to empirics, and which serves as a foundation to guide practice. To facilitate this theory development, we outline a set of ways that a new theory of value would need to differ from the dominant economic (utility) theory of value in order to explain what is known about the multiple values of nature. Whether by illustrating and enlivening an existing alternative theory of value or by inspiring a new theory, perhaps this fledgling field of the multiple values of nature is poised to disrupt much broader understandings of what matters to people and why. Read the free Plain Language Summary for this article on the Journal blog.